Tourism development in santa fe as a popular beach on bantayan island: local perceptions analysis¬¬¬¬ - GIDO, NATHANIEL G.; REYAN D. DIAZ; ISRAEL N. ABARRATIGUE. DM; JULIUS ALGNE NIÑO D. BATIANCILA; ALJOHN P. MANSUETO (International Journal of Multidisciplinary Research and Studies, 2023)
This study assessed these impacts through the analysis of local perceptions based on four criteria of tourism development – the economic, environmental, social, and cultural impacts using a five-point Likert scale in order to create a sustainability plan for the progress of Santa Fe Beach Resort. Overall, the community had low satisfaction with tourism development and perceived it as needing improvement. The total average score of the four criteria was below the average (SD: 3.57 ± 0.91). Tourism development had produced adverse environmental and cultural effects. In general, the results do not show a significant difference in the perceived tourism impact between males and females. However, the results reveal that the FSs perceived that the costs and benefits of tourism development impacts are associated with the FS level of knowledge. The perceived negative impact of tourism was addressed in the primary school group with the lowest scores. This group perceived the adverse effects on four criteria: economic (SD: 3.63 ± 1.02), environmental (SD: 3.68 ± 0.86), social (SD: 3.60 ± 0.95), and cultural (SD: 3.37 ± 0.81). The FSs’ profiles revealed that the social transformation in the communities to an urban lifestyle may change the local attitudes toward tourism meaning their economic position and tourism benefits may far outweigh its cost.